(untitled) (Research, Society and Development, 2021)
4-hydroxycoumarin (4H) is a natural and synthetic phenolic compound that presents important attributes, including anti-HIV, antitumor, and anticoagulant properties. Considering its important biological activities and the use of 4H, the aim of this present study was to investigate the toxic, mutagenic, antimutagenic, and antioxidant activities of 4H, commercially obtained, in experiments in vivo and in vitro. The effects of acute oral administration at a dose of 200 mg/kg of 4H were investigated by the hippocratic screening in animals. The micronucleus assay on peripheral blood and the Ames test were used for analysis of mutagenicity, while the antimutagenicity was tested against cyclophosphamide also by in vivo micronucleus assay. For all in vivo tests were used Swiss mice. The antioxidant activity was determined by the capacity of the 4H sample to sequester the stable 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical. The results showed that 4H no induced changes in the behavior or the histology of treated animals neither mutagenic activity (genic or chromosomal). On the other hand, it exhibited a protective effect against cyclophosphamide and antioxidant potential. 4- hydroxycoumarin is widely used clinically as a precursor molecule in the synthesis of synthetic anticoagulant drugs. Therefore, the results obtained are extremely important, as they demonstrate the absence of mutagenic potential and protection against chromosomal damage.